Effect of Nigella Sativa and Allium Sativum Coadminstered with Simvastatin in Dyslipidemia Patients: A Prospective, Randomized, Double-Blind Trial - Hamed Ahmad Alobaidi, Amina (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2014)
Dyslipidemia plays an important role in the provocation of cardiovascular disease. Psoriasis was associated with metabolic disorder and therefore the present study was performed to evaluate the therapeutic effect of combination of blackseed with garlic as a treatment for dyslipidemia. A randomized, double-blind, placebo controlled, two arms parallel study consisted of 4 week diet stabilization period that included a 4 week base line evaluation phase, followed by an 8 week treatment period. The study comprised men (n=127) and women (n=131) aged 24 to 57 years, who met the NCEP ATP III criteria for drug treatment of hyperlipidemia and dietary intervention. Three hundred patients were randomized to treatment and 258 completed the study. The lipid profile included total cholesterol, HDL-C, Non-HDL-C, LDL-C, and Triglyceride. There were no significant differences between the two treatment groups at the baseline for triglyceride, HDL, Non-HDL, LDL and total cholesterol. Following 8 weeks treatment with simvastatin plus placebo the reduction in Non-HDL, triglyceride, LDL and total cholesterol following treatment course was statistically highly significant (P= <0.01). However, the increase in HDL was significant (P=0.02). Patients who received simvastatin, plus black seed and garlic for 8 weeks of treatment show significant differences between baseline and after treatment course for all tested profiles (P=<0.01). This comparison of mean values reveals a high significant difference (P=<0.01) for cholesterol, triglyceride, Non-HDL, and LDL, and significant difference (P=0.03) for HDL between the two treatment groups. This study suggests that the evaluated combination was effective in correction of dyslipidemia. Large scale clinical trials comparing different doses are warranted.
Keywords: triglyceride